A Simplified Numerical Method for Blast Induced Structural Response Analysis - Li, Jun; Hao, Hong (Multi-Science Publishing, 2014)
Efficiently and accurately predicting structural dynamic response and damage to external blast loading is a big challenge to both structural engineers and researchers. The conventional numerical treatment to this problem is proved being able to give reliable predictions, however at the cost of enormous computational time and resource. Simplified SDOF approach is popularly used in design as it is straightforward to use and also gives good structural response predictions if the response is governed by a global response mode (shear or bending) and the accurate dynamic deflection curve is available, but it cannot predict the detailed local structural damage. In this study, a new numerical approach that combines the recently proposed two-step method and the static condensation method is proposed to analyze structure response and collapse to blast loads. The two-step method divides the structural response into two phases, i.e. forced vibration phase (blastloading duration) and free vibration phase. Single- Degree-of-Freedom system approach is adopted to solve the structural element responses at the end of the forced vibration phase, and the structural free vibration simulation is carried out using the hydro-code LS-DYNA to calculate the detailed structural response and damage. The static condensation technique is utilized to condense structural components that are relatively away from the explosion center to further reduce the computational effort. To demonstrate the proposed method, the structural responses of a three story RC frame to blast loads are calculated by four approaches, i.e. the traditional detailed FE simulation, the two-step method, the model condensation method, and the new combined two-step and dynamic condensation method. Through the results comparison, the efficiency and accuracy of the proposed combined approach are demonstrated.